Disseminated tuberculosis in a lung transplant recipient presenting as tenosynovitis, subcutaneous nodules, and liver abscesses. (October 2022) - Vargas Barahona, Lilian; Henao-Cordero, José; Smith, Joshua; Gray, Alice; Marshall, Carrie B.; Scherger, Sias; Bajrovic, Valida; Koullias, Yiannis
Tuberculosis is of particular concern in lung transplant recipients. We present the case of a patient who received a double lung transplant from a deceased donor from Mexico and developed disseminated tuberculosis 60 days post-transplant manifested as tenosynovitis, liver abscesses, and subcutaneous nodules with no definitive lung allograft involvement. The recipient did not have evidence of tuberculosis on explanted lungs, had a negative interferon gamma release assay pre-transplant, and did not have risk factors for this infection. Mycobacterium tuberculosis should remain in the differential diagnosis of early post-transplant infections with atypical presentations, evidence of dissemination, or lack of improvement with appropriate antimicrobial coverage, even in the absence of typical lung findings.